The impact of green trade barriers on China’s photovoltaic products exports to ASEAN - Chen, Shumin (Frontiers in Environmental Science, 2024)
In the context of the global push towards a green economy, this research investigates the impact of green trade barriers on the export trade volume of Chinese photovoltaic products to ASEAN from 2010 to 2021. The strong evidence indicates that green trade barriers have a positive effect on improving the export trade volume of Chinese photovoltaic products to ASEAN. This conclusion remains robust through multiple robustness tests, including excluding data from pandemic-affected years and the only developed country Singapore. Moreover, the impact of green trade barriers varies with exchange rate levels and language environments. In countries with higher exchange rates and countries with different official languages, the positive effect of green trade barriers on trade is more significant. In contrast, in countries with the same official language, green trade barriers have a negative effect on improving the trade volume. Additionally, higher levels of renewable energy consumption diminish the beneficial effect of TBT on photovoltaic trade, and CO2 emissions lessen the detrimental effect of TBT on photovoltaic trade. The findings provide valuable insights for policymakers, suggesting that align with international standards, provide differentiated technical assistance and adopt transparent trade rules when formulating green trade barriers to better support the competitiveness and export growth of Chinese photovoltaic products in the international market.